Bacterial community compositions of coking wastewater treatment plants in steel industry revealed by Illumina high-throughput sequencing. (March 2015) - Ma, Qiao; Qu, Yuanyuan; Shen, Wenli; Zhang, Zhaojing; Wang, Jingwei; Liu, Ziyan; Li, Duanxing; Li, Huijie; Zhou, Jiti
Graphical abstract: Highlights: Nine activated sludges from coking wastewater treatment plants were sequenced. Thiobacillus, Comamonas, Thauera, Azoarcus and Rhodoplanes were the core genera. Percentages of AOB and NOB were low. Operation mode, temperature and flow rate affected community formation. Abstract: In this study, Illumina high-throughput sequencing was used to reveal the community structures of nine coking wastewater treatment plants (CWWTPs) in China for the first time. The sludge systems exhibited a similar community composition at each taxonomic level. Compared to previous studies, some of the core genera in municipal wastewater treatment plants such as Zoogloea, Prosthecobacter and Gp6 were detected as minor species. Thiobacillus (20.83%), Comamonas (6.58%), Thauera (4.02%), Azoarcus (7.78%) and Rhodoplanes (1.42%) were the dominant genera shared by at least six CWWTPs. The percentages of autotrophic ammonia-oxidizing bacteria and nitrite-oxidizing bacteria were unexpectedly low, which were verified by both real-time PCR and fluorescence in situ hybridization analyses. Hierarchical clustering and canonical correspondence analysis indicated that operation mode, flow rate and temperature might be the key factors in community formation. This study provides new insights into our understanding of microbial community compositions and structures of CWWTPs.